An Epidemiological Trend of Urogenital Schistosomiasis in Ethiopia - Chala, Bayissa; Torben, Workineh (Frontiers in Public Health, 2018)
Schistosomiasis is a major public health problem in Ethiopia. Currently, the prevalence of the disease can possibly be heightened due to man-made ecological transformations particularly related to the recent development programs involving irrigation and construction of dams. The expansion of some of the water resource development projects has been cited enhancing the upsurge of urogenital schistosomiasis mainly in the lower altitude areas of the country. In connection to the extensive initiation of development projects in low altitude areas of the country, simultaneous and adequate attentions have never been given to address a pre-assessment of health impacts of the development programs prior to launching the projects. Helpful appraisals focusing on evaluation of epidemiology of urogenital schistosomiasis in Ethiopia have not been explored. Therefore, the current review attempts to trace an overall picture of the epidemiological status of urogenital schistosomiasis in the country; the past and existing trends of urogenital schistosomiasis surveys and control programs of the country are reviewed. Essential recommendations are highlighted for possible inputs in future control design strategies of national control program of schistosomiasis.